Attributability and Agency: Moral Attributability for Mental States as Possession of Care-constitutive Desires - (:unkn) unknown (My University, 2018)
A prominent line of thought owed originally to the work of Harry Frankfurt is that it is our identifying, in a certain technical sense, with our mental states which makes these states and the actions which emerge from them our own in a way distinctive of agents. Separately, moral attributability, a sort of responsibility located first by T. M. Scanlon, has recently attracted the attention of many philosophers. In this paper I will argue that we ought to aim to adopt theories of identification and moral attributability such that our capacity for the sort of agency involved in identification is a precondition for our capacity to have mental states attributable to us. Motivated by this point and the prominent line of thought that we identify through our cares, I will develop an account of moral attributability through caring, for which I argue it is plausible such an explanatory relationship can exist between our capacities for identification and attributability.
Keywords: Attributability; Care; Identification; Responsibility